Psychometric Properties of the Suicide Stroop Task in a Chinese College Population - Niu, Lu; Feng, Xia; Jia, Zhouxin; Yu, Yu; Zhou, Liang (Frontiers in Psychology, 2021)
Objective: This study aimed to test the psychometric properties of the Suicide Stroop Task in Chinese college population. Methods: College students (n=121) who were in the 1st-4th grade, fluent in Chinese, and without color-blindness were recruited from a university in Guangzhou, China during September to December, 2019. Participants were administered to the Suicide Stroop Task at baseline and 1-month follow-up. Results: The Suicide Stroop Task showed excellent internal reliability (Cronbach’s α ranged from 0.940-0.953). However, the Suicide Stroop Task did not reveal suicide related attentional biases among current suicide ideators, and was not significantly associated with the severity of suicidal ideation, depression, hopelessness, nor anhedonia (all p values >0.05), indicating a lack of concurrent validity for the task. Additionally, the 2-time data of interference scores could not generate intraclass correlation coefficients (ICC) due to a negative average covariance among data, which indicated poor test-retest consistency for the task. Conclusion: The results of this study did not support the use of the Suicide Stroop Task on identification suicidal risk among Chinese college students. It is crucial to assess psychometric properties of behavioral measures rigorously as self-report measures before large applications in clinical and community settings.